Archaeological prospecting using the Electric Resistivity Imaging method at the Borsippa site, Near Babylon, Central Iraq - Berhi, Fatima Z.; Al-Saadi, Osamah S. (Iraqi Journal of Science, 2024)
Many important archaeological sites in Iraq still need to be preserved. Some of these sites were subjected to destruction and negligence. So, exploring these sites represents a priority for its protection. A 2D Electrical Resistivity Imaging (ERI) as a non-invasive geophysical survey method was implemented at a part of the Borsippa archaeological site near Babylon to search for the subsurface archaeological artefacts/structures. Electrical resistivity measurements were carried out using a Dipole-Dipole array. Steps were taken to process and filter using Horizontal profiles, forward modelling, and 2D inverse models to analyze the resistivity measurements. The ERI inversion results show that the superficial conductive zone produced variations in ERI inverse models. The low resistivity caused by the relatively high conductivity was observed due to rainwater leaking into the topsoil zone. The ERI sections revealed a coherent depth of approximately 7 meters and the anomalies geometry and semi-layering soil. These changes can be attributed to the high resistivity contrast between the relatively high-resistivity anomalies and the surrounding intact soil. The soil types include dry silty and clayey soils and crushed refractory materials such as broken bricks and ruins mixed with rock pulp. These materials have resulted in the collapse of walls due to weathering and erosion. Based on the identified patterns, shallow-depth high-resistive anomalies are present and extend throughout some parts of the study area. These anomalies are represented in a SW-NE trend of the mound area. At the bottom of this zone is another zone with low resistance values and variable thickness, which varies from place to place within the study area. The results proved the efficiency of the ERI technique in detecting archaeological wall-like artefacts, which represents a data bank for any future archaeological prospection.